The Biochemical, Hematological and Histopathological Changes study induced by Tramadol and treated by Curcumin in Local Male Rabbits - Mahmood, Mohammed Abed (Diyala Journal for Veterinary Sciences, 2023)
The goal of current study to study the antioxidant effect of curcumin on biochemical, hematological parameters and histopathological effect on liver and kidney in male local rabbits. Twenty local male rabbits were used and divided randomly and equally into four groups, each groups with fife rabbits. The first group injected with normal saline for two weeks. The second group given curcumin powder 50 mg/kg dissolved on corn oil by stomach tube daily for two weeks. Third group give tramadol tablets 200mg/kg one dose daily for two weeks and the four groups give curcumin followed by tramadol one dose for two weeks. The biochemical result showed no obvious difference between control group and second group, Group three showed increase in AST,ALT and ALP but these value return to normal in four group, total protein and albumin relatively normal in first ,second and four group while in third group showed decrease in value of it. The hematological parameters showed no difference of WBC in third group while the RBC and hemoglobin decrease in third group which treated with tramadol only, Platelets showed normal value in first, second group but decrease in third group . The histopathological study in liver showed normal histological section in first and second group, third group showed congestion of central portal vein, hepatocytic degeneration and congestion of sinosoids. In kidney the first, second group showed normal appearance of kidney structures but in the third group when used tramadol , the kidney showed enlarged hepatic vein, fibrosis and congestion of glumeruli. The used of curcumin before tramadol lead to decrease the histopathological lesion in both liver and kidney.